HEPATOGENOUS PHOTOSENSITIZATION OUTBREAK IN CATTLE ASSOCIATED WITH UROCHLOA SPP. INGESTION IN SOUTHEASTERN RIO GRANDE DO SUL, BRAZIL - Yasmin Binow de Alvarenga; Yris Márcia Bastos Baldon; Amanda Pratissoli Pancieri; Luisa Frasson Vieira; Amanda Thereza Cabalini Ziviani; Plínio Aguiar de Oliveira; Haide Valeska Scheid; Clairton Marcolongo Pereira (UNESC em Revista, 2025)
Hepatogenous photosensitization is a non-infectious toxic disease affecting ruminants in several regions of Brazil, mainly caused by the ingestion of grasses of the genus Urochloa spp. (syn. Brachiaria spp.). These plants contain lithogenic steroidal saponins that induce cholangiopathic lesions and phylloerythrin retention, resulting in photosensitive dermatitis in non-pigmented areas. This study aimed to report an outbreak of hepatogenous photosensitization in cattle associated with Urochloa spp. ingestion on a farm in Turuçu, southern Rio Grande do Sul, Brazil. Eleven cases were recorded, with a case fatality rate of 45%. Clinically, affected animals showed ulcerative skin and tongue lesions, desquamation of the labial mucosa, epiphora, and brisket edema. Grossly, the liver was enlarged and yellowish, and histopathology revealed hepatocellular vacuolation and bile pigment accumulation consistent with cholestasis. No birefringent crystals were observed. The clinicopathological findings confirmed hepatogenous photosensitization secondary to Urochloa spp.. Ingestion. This report expands the geographic occurrence of the disease in southern Brazil and emphasizes the importance of monitoring pastures to prevent further outbreaks. Keywords: cattle, cholestasis, photosensitive dermatitis, toxic plants, steroidal saponins.